Alternative Financing for Energy Efficiency Saving in Indonesia Under LCCA Analysis - Sudarmaji, Eka; Ardianto, Yuli (International Journal of Psychosocial Rehabilitation, 2020)
Under the LCCA system, we present the calculation of the “investment cost” on energy efficiency saving. This paper to set up an initial model in developing the model for Energy Saving Companies in Indonesia in assessing alternative financing for Energy Efficiency Saving in Indonesia. The reviewed for all the energy efficiency saving advantages cover the upfront investment costs are presented. The model is using the Analytic Hierarchy Process (AHP) and life cycle cost (LCC) analysis, with sensitivity analysis, is presented under possible a game-theory process. On some occasion, these alternative financing values are comparing to other similar investment returns as well as the risks.